Mining for peace - Hodler, Roland,Schaudt, Paul,Vesperoni, Alberto (CESifo, 2023)
The energy transition increases the demand for minerals from ethnically diverse, conflict-prone developing countries. We study whether and where mining is possible in such countries without raising the risk of civil conflict. We proceed in three steps: First, we propose a theoretical model to predict the occurrence and location of conflict events on the territory of a country based on the spatial distribution of ethnic groups and resource rents. Second, we verify the predictive power of this model using granular spatial data from Sierra Leone and confirm its broader applicability using less granular data from a sample of eight West African countries. Third, we employ our framework to simulate the potential impact of new (planned and unplanned) mining projects in Sierra Leone. A crucial insight is that new mining projects do not necessarily translate into more conflict but may pacify the country under the right conditions and the right policies.
10419/271851
Keywords: Graue Literatur; civil conflict; ethnic conflict; natural resources; mining